17-β-Estradiol Upregulates the Stress Response in Candida albicans: Implications for Microbial Virulence. Issue 4 (1998) - O'Connor, C.; Essmann, M.; Larsen, B.
Abstract : Objective: The influence of 17-β-estradiol on the stress response of Candida albicans was studied. Methods: The survival of clinical isolates of C. albicans treated with 17-β-estradiol after heat and oxidative stress was measured by viable plate counts. Cellular proteins were analyzed via SDSPAGE. Results: The heat stress response induced by 17-β-estradiol in C. albicans grown at 25 ℃ protected the organisms against the lethal temperature of 48.5 ℃, as shown by viable plate counts. 17-β-estradiol also enhanced protection of C. albicans against oxidative stress (menadione exposure). SDS-PAGE analysis of cytoplasmic extracts revealed proteins induced by 17-β-estradiol were similar to those induced by heat. Conclusion: 17-β-estradiol enhances survival of C. albicans under heat and oxidative stresses. The proteins induced by 17-β-estradiol are probably heat shock proteins. Because heat shock proteins are considered to be virulence factors, 17-β-estradiol may function to promote in vivo survival.